E-pedagogy: Technology Matters in Mathematics Education - Dhakal, Bed Prasad (Educational Journal, 2024)
Growing culture of internet and technology use in Nepal has introduced new landscape of educational practices. These practices are growing in the form of e-pedagogy: technology integrated teaching and learning activities. In this context, this paper has explained engaged and interactive learning environment in higher mathematics education in Nepal. An action research intervention of VLE (Virtual Learning Environment for Mathematics) was carried out in a cohort of 170 master students in a course Differential Geometry at Central Department of Education, Tribhuvan University, Kirtipur, Kathmandu, Nepal. The instrument used in this study were baseline and end line survey questionnaire, interview-guideline and VLE generated log reports. The collected data were analyzed with descriptive statistics and themes using SPSS and Atas.ti. The results of the study showed that M-VLE as e-pedagogy helped students (a) to increase learning presence anytime anywhere, (b) to enhance personalized learning experience, and (c) to provide timely and recursive learning feedback and support. Therefore, the study concluded that e-pedagogy matters in higher mathematics education for engaged and interactive learning of higher mathematics.